Efektivitas PowerPoint dan Quizizz dalam Meningkatkan Pembelajaran Al-Quran dan Hadis: Studi Kasus MA Al Hikam Jombang - Febrian, Fikri Al Huda (Maliki Interdisciplinary Journal, 2024)
Teachers play a crucial role in implementing discipline in schools, where they act as parents to their students. Teachers bear a significant responsibility in shaping students’ character; therefore, they must serve as positive examples for their students. The role of teachers in disciplining students is not only about enforcing rules but also about shaping character, reinforcing values, and preparing students to become responsible individuals who contribute positively to society. Habitual violation of school rules without any decisive action will have adverse effects on students; they will tend to disregard the rules because they feel there are no consequences for their actions. Therefore, decisive actions are necessary for students who violate rules. The research method employed is qualitative descriptive, utilizing books, journals, articles, etc., as references. Additionally, direct observation at the school was conducted to understand the conditions firsthand.